Modern HPLC for practicing scientists [ - Dong, M. W. (Wiley-Interscience, 2006)
A comprehesive yet concise guide to Modern HPLC Written for practitioners by a practitioner, Modern HPLC for Practicing Scientists is a concise text which presents the most important High-Performance Liquid Chromatography (HPLC) fundamentals, applications, and developments